(untitled) (Journal of Geography and Environmental Management, 2021)
Currently, the study of atmospheric parameters that hinder the flight of aircraft and cause damage to aviation equipment is one of the most important issues of meteorological support for aviation. Meteorological support-one of the factors taken into account in the organization, execution, maintenance of flights and air traffic control is the weather. Its main goal is to ensure flight safety. Meteorological parameters and phenomena that are dangerous for aviation can cause serious damage to airlines, including the airport of Almaty. Therefore, the study of the distribution of meteorological parameters affecting aircraft at the airport of Almaty is one of the urgent problems at the present time. This article examines the features of the distribution of meteorological parameters over height for the period 2013-2017. at the airport in Almaty. The following meteorological parameters affecting aircraft (AC) were analyze: air temperature, atmospheric pressure, wind speed and direction, type and size of clouds, as well as the following hazardous phenomena affecting the height: aircraft turbulence, aircraft icing, jet flow, etc. Meteorological data in the form of upper-air diagrams were taken from the Internet from flymeteo.org.